Michelin Is Coming to Town: Organizational Responses to Status Shocks - Favaron, Saverio Dave; Di Stefano, Giada; Durand, Rodolphe (Management Science, 2022)
What happens in the aftermath of the introduction of a new status ranking? In this study, we exploit the unique empirical opportunity generated by the release of the first edition of the Michelin Guide for Washington, DC, in the fall of 2016. We build on prior work on rankings as insecurity-inducing devices by suggesting that newly awarded high-status actors modify their self-presentation attributes to fit with what they believe audiences expect from the elite. Our results show that, depending on their standing prior to Michelin’s entry, restaurants acted upon different attributes of their self-presentation. Restaurants with high prior standing emphasized attributes that channeled authenticity and exclusivity, which may imply that their Michelin designation triggered operational changes. Actors with low prior standing, on the other hand, acted on descriptive attributes that did not necessarily imply operational changes and could be easily manipulated to signal their belonging among the elite. We contribute to research on status and conformity by disentangling the sources and types of conformity behaviors that newly awarded high-status actors deploy. This paper was accepted by Lamar Pierce, organizations.